Analisis Kinerja Keuangan PT. Bank Perkreditan Rakyat (BPR) Mitra Lestari terhadap Tingkat Kesehatan Perbankan - Endah Tri Kurniasih; Iqra Wiarta; Beny Pebryansa (Ekonomis: Journal of Economics and Business, 2020)
The level of health in the financial services industry is important, both for consumers and for management. The banking sector itself must have a level of health that refers to regulations regulated by Bank Indonesia. One of the companies engaged in banking sector in Jambi City is PT. Bank Perkreditan Rakyat Mitra Lestari. This research aims to find out and analyze the health level of PT Bank Perkreditan Rakyat Mitra Lestari based on profitability ratio and liquidity ratio. The results of this study are: The health level of PT Bank Perkreditan Rakyat Mitra Lestari is seen from the Provitability Ratio judging by the ratio of Return On Asset (ROA) especially in 2014, 2016, 2017 and 2018 obtained healthy predicate, this means that in that period PT BPR Mitra Lestari managed to optimize the assets owned to gain profit (Profit). The health level of PT Bank Perkreditan Rakyat Mitra Lestari is seen from liquidity ratio which is cash ratio (CR) always got healthy predicate. And from the results of the analysis can be concluded that to fulfill /pay obligations to customers who have invested their funds in the credit provided during the period 2014-2018 PT Bank Perkreditan Rakyat Mitra Lestari has been very good, this can be seen from the loan to deposit ratio (LDR) ratio always got a healthy predicate.